Nitrogen and phosphorous recycling from human urine by household electrochemical fixed bed in sparsely populated regions. (30th June 2022) - Hao, Jingwei; Zeng, Huabin; Li, Xuewei; Zhang, Yifeng; Lei, Yang; Sheng, Guoping; Zhao, Xu
Highlights: An electrochemical system was divisionally packed by magnesite/carbon for N/P recovery. Nitrogen and phosphorus were recovered by struvite precipitation and ammonia. The electrogenerated acid-base zone optimizes the solution pH for N/P recovery. The employment of struvite in nurturing garden is a low-carbon fertilization model. Abstract: Decentralized treatment of human urine in sparsely populated regions could avoid the problem of sewage collection in traditionally centralized treatment schemes and simultaneously utilize the recovered N/P fertilizer in-situ to nurture gardens. Herein, an integrated electrochemical fixed bed packed with divided magnesite and carbon zones was constructed for the pretreatment of human urine, followed by the recovery of 95.0% NH4 + and 85.8% PO4 3− via struvite precipitation and NH3 volatilization as well as the on-site employment of the produced struvite as fertilizer. In the process, the acid/base zones created by electrochemical water splitting dissolved the magnesite filler as the Mg 2+ source of struvite, further creating an ideal pH environment for struvite precipitation and NH3 volatilization in the effluent. Without the need to control solution pH by chemical addition, the system can resist impacts from changes in water quality by adjustment of the current density and flow rate, indicating its great potential for automatic operation. Life cycle assessment indicated that the on-site employment of produced struvite avoids the long-distance fertilizer transportation required for fertilization, thus reducing carbon emission by a hundred million tons per year if the household facility is driven by clean electricity. Graphical abstract: Image, graphical abstract